The approach to 4d/4f-polyphosphides. Issue 12 (29th September 2015) - Arleth, Nicholas; Gamer, Michael T.; Köppe, Ralf; Pushkarevsky, Nikolay A.; Konchenko, Sergey N.; Fleischmann, Martin; Bodensteiner, Michael; Scheer, Manfred; Roesky, Peter W.
Abstract : The first 4d/4f polyphosphides were obtained from reactions of the divalent metallocenes [Cp*2 Ln(thf)2 ] (Ln = Sm, Yb) with [CpMo(CO)2 2 (μ, η 2:2 -P2 )] or [Cp*Mo(CO)2 (η 3 -P3 )]. New aggregation of the central phosphorus scaffold in combination with P–P bond formation within the coordination sphere of the transition metal was observed. Abstract : The first 4d/4f polyphosphides were obtained by reaction of the divalent metallocenes [Cp*2 Ln(thf)2 ] (Ln = Sm, Yb) with [CpMo(CO)2 2 (μ, η 2:2 -P2 )] or [Cp*Mo(CO)2 (η 3 -P3 )]. Treatment of [Cp*2 Ln(thf)2 ] (Ln = Sm, Yb) with [CpMo(CO)2 2 (μ, η 2:2 -P2 )] gave the 16-membered bicyclic compounds [(Cp2 *Ln)2 P2 (CpMo(CO)2 )4 ] (Ln = Sm, Yb) as the major products. From the reaction involving samarocene, the cyclic P4 complex [(Cp*2 Sm)2 P4 (CpMo(CO)2 )2 ] and the cyclic P5 complex [(Cp*2 Sm)3 P5 (CpMo(CO)2 )3 ] were also obtained as minor products. In each reaction, the P2 unit is reduced and a rearrangement occurred. In dedicated cases, a P–P bond formation takes place, which results in a new aggregation of the central phosphorus scaffold. In the reactions of [Cp*2 Ln(thf)2 ] (Ln = Sm, Yb) with [Cp*Mo(CO)2 P3 ] a new P–P bond is formed by reductive dimerization and the 4d/4f hexaphosphides [(Cp*2 Ln)2 P6 (Cp*Mo(CO)2 )2 ] (Ln = Sm, Yb) were obtained.